Seroprevalence of Human Brucellosis among the Population at Risk in Rural Area - Muhammad, N; Hossain, MA; Musa, AK; Mahmud, MC; Paul, SK; Rahman, MA; Haque, N; Islam, MT; Parvin, US; Khan, SI; et al. (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):1-4. The abstract of this article is available on the PubMed website